Research progress and hotspot of the artificial intelligence application in the ultrasound during 2011–2021: A bibliometric analysis - Xia, Demeng; Chen, Gaoqi; Wu, Kaiwen; Yu, Mengxin; Zhang, Zhentao; Lu, Yixian; Xu, Lisha; Wang, Yin (Frontiers in Public Health, 2022)
Ultrasound, as a common clinical examination tool, inevitably has human errors due to the limitations of manual operation. Artificial intelligence is an advanced computer program that can solve this problem. Therefore, the relevant literature on the application of artificial intelligence in the ultrasonic field from 2011 to 2021 was screened by authors from the Web of Science Core Collection, which aims to summarize the trend of artificial intelligence application in the field of ultrasound, meanwhile, visualize and predict research hotspots. A total of 908 publications were included in the study. Overall, the number of global publications is on the rise, and studies on the application of artificial intelligence in the field of ultrasound continue to increase. China has made the largest contribution in this field. In terms of institutions, FUDAN UNIVERSITY has the most number of publications. Recently, IEEE ACCESS is the most published journal. SURI JS published most of the articles and had the highest number of citations in this field (29 articles). It's worth noting that, convolutional neural networks (CNN), as a kind of deep learning algorithm, was considered to bring better image analysis and processing ability in recent most-cited articles. According to the analysis of keywords, the latest keyword is "COVID-19" (2020.8). The co-occurrence analysis of keywords by VOSviewer visually presented four clusters which consisted of “deep learning”, “machine learning”, “application in the field of visceral organs” and “application in the field of cardiovascular”. The latest hot words of these clusters were “COVID-19; neural-network; hepatocellular carcinoma; atherosclerotic plaques”. This study reveals the importance of multi-institutional and multi-field collaboration in promoting research progress. In addition, through analyzing the research trend in this field, Deep Learning (DL) algorithm that included CNN method will become the direction of research in the future.